“Double-Lumen Valve-Controlled Intra-Operative Pyeloplasty Stent (VIPs)”: A New Technology for Post-Pyeloplasty Stenting – Proof of Concept Study in a Preclinical Large Animal Model - Tariq Osman Abbas (18148378) (2020)
Background Pyeloplasty is a common surgical operation with a high success rate. However, significant challenges are to be optimized in the design of stenting systems in order to improve perioperative monitoring of urine drainage and enhance patient and family comfort through easier post-operative care. Materials and Methods In a preliminary study in six pigs, handling, mechanical and functional features of this stent system were tested. In our main study, six double-lumen stents (230 mm long each) and 6F/9F external diameter were implanted through the ureteric walls of six domestic pigs to allow postoperative drainage and monitoring following ureteroureterostomy. After a 7-day survival period, monitoring with intravenous antibiotic coverage, and pain control, contrast antegrade pyelogram, under valve control, and renal ultrasonography were conducted and stents explanted and the animals were then euthanized. Results The double-lumen valve-controlled stent supported the healing of the neo anastomoses and helped to monitor perioperative urine drainage and perianastomotic leakage accurately. It also guided a well-controlled more informative radiological contrast-supported imaging before removal of the stents that confirmed the healing of the neo anastomotic site and no leak formation. The double-lumen system demonstrated high feasibility regarding its insertion, functionality, and removal capacities. The excellent flexibility of the individual stents allowed exact anatomically controlled implantation. Conclusion The double-lumen valve-controlled stent system was studied in a porcine model, which demonstrated its feasibility. Preclinical experience revealed favorable results concerning stent implantation, operability and functionality, in the perioperative management of pyeloplasty or ureteric surgery. Other Information Published in: Research and Reports in Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/rru.s238572